A New Watermarking Scheme for Medical Images with Patient’s Details - Nagaraju, G; Pardhasaradhi, P; S. Ghali, V (International Journal of Engineering and Technology, 2018)
A brain tumor is a mass of cells in your brain that are not normal.Some brain tumors contain cancer and others don't: Brain tumor include both, benign and malignant forms. Benign brain tumors don't have cancer cells. Malignant brain tumors have cancer cells. Differentiating malignant and benign cases is a hard task even for experienced specialists. This work presents how to extract the characteristics and features of tumor image by general segmentation methods for malignant risk computation and presents the use of digital watermarking for applications of automated tumor image analysis. Here personal information such as name, age, gender, location, ADHAAR number, contact number etc., and tumor information such as tumor types, area of the tumor, severity, and any other useful information are embedded to the tumor image. Encrypting that image with well-known encryption algorithms is also possible to avoid unnecessary nuisance from information hackers.